Ayahuasca blocks ethanol preference in an animal model of dependence and shows no acute toxicity - Gianfratti, Bruno; Tabach, Ricardo; Sakalem, Marna Eliana; Stessuk, Talita [UNESP]; Maia, Lucas Oliveira; Carlini, Elisaldo Araujo (Elsevier, 2022)
Ethnopharmacological relevance: Ayahuasca, a psychoactive beverage prepared from Banisteriopsis caapi and Psychotria viridis, is originally used by Amazon-based indigenous and mestizo groups for medicinal and ritualistic purposes. Nowadays, ayahuasca is used in religious and shamanic contexts worldwide, and preliminary evidence from preclinical and observational studies suggests therapeutic effects of ayahuasca for the treatment of substance (including alcohol) use disorders. Aim of the study: To investigate the initial pharmacological profile of ayahuasca and its effects on ethanol rewarding effect using the conditioned place preference (CPP) paradigm in mice. Materials and methods: Ayahuasca beverage was prepared using extracts of B. caapi and P. viridis, and the concentration of active compounds was assessed through high performance liquid chromatography (HPLC). The following behavioral tests were performed after ayahuasca administration: general pharmacological screening (13, 130, or 1300 mg/kg – intraperitoneally – i.p., and 65, 130, 1300, or 2600 mg/kg – via oral – v.o.); acute toxicity test with elevated doses (2600 mg/kg – i.p., and 5000 mg/kg – v.o.); motor activity, motor coordination, and hexobarbital-induced sleeping time potentiation (250, 500, or 750 mg/kg ayahuasca or vehicle – v.o.). For the CPP test, the animals received ayahuasca (500 mg/kg – v.o.) prior to ethanol (1.8 g/kg – i.p.) or vehicle (control group – i.p.) during conditioning sessions. Results: Ayahuasca treatment presented no significant effect on motor activity, motor coordination, hexobarbital-induced sleeping latency or total sleeping time, and did not evoke signs of severe acute toxicity at elevated oral doses. Ayahuasca pre-treatment successfully inhibited the ethanol-induced CPP and induced CPP when administered alone. Conclusions: Our results indicate that ayahuasca presents a low-risk acute toxicological profile when administered orally, and presents potential pharmacological properties that could contribute to the treatment of alcohol use disorders.
Keywords: Ayahuasca; DMT; Ethanol abuse; Medicinal plants; Psychotropic drugs